Arkansas Juvenile Court Records, 1991-1993 ([Verlag nicht ermittelbar], 1998)
This data collection describes in quantitative terms the volume of juvenile cases disposed by courts having jurisdiction over juvenile matters (delinquency, status offense, and dependency cases). Inaugurated in 1983, the Arkansas Administrative Office of the Courts began to collect data from intake and probation departments on each case disposed during the previous calendar year. The data include a record of each case processed formally with petition for each delinquency, dependent/neglect, or family in need of services case disposed. Information is provided on county, case type, date of filing, reason for referral to the courts, and the court action.